Concerns of Women of Reproductive Age with Multiple Sclerosis: A Qualitative Study - Alizadeh, Tajdar; Keshavarz, Zohreh; Mirghafourvand, Mojgan; Zayeri, Farid (Advances in Nursing & Midwifery, 2018)
Abstract Introduction: Psychological disorders are the leading cause of disabilities, social harms, and reduced quality of life in patients with Multiple Sclerosis (MS). This qualitative study was conducted to describe the concerns of females with MS. Methods: In this qualitative study, 16 females with MS at the reproductive age with medical records at the MS Society of Tabriz were selected using the purposive sampling technique and underwent semi-structured in-depth individual interviews. All interviews were recorded, transcribed, and analyzed using conventional content analysis. Results: In this study, 23 codes were identified from transcribed interviews and categorized to two sub-categories, fears and feelings. These two sub-categories formed the main category, named concerns. Conclusions: Regarding concerns of these patients, their regular health monitoring by physicians and healthcare providers is recommended in an attempt to alleviate these concerns.